Hydrogen and Carbon Monoxide-Utilizing Kyrpidia spormannii Species From Pantelleria Island, Italy - Hogendoorn, Carmen; Pol, Arjan; Picone, Nunzia; Cremers, Geert; van Alen, Theo A.; Gagliano, Antonina L.; Jetten, Mike S. M.; D’Alessandro, Walter; Quatrini, Paola; Op den Camp, Huub J. M. (Frontiers in Microbiology, 2020)
Volcanic and geothermal areas are hot and often acidic environments that emit geothermal gasses, including H2, CO and CO2. Geothermal gasses mix with air, creating conditions where thermoacidophilic aerobic H2- and CO-oxidizing microorganisms could thrive. Here, we describe the isolation of two Kyrpidia spormannii strains, which can grow autotrophically by oxidizing H2 and CO with oxygen. These strains, FAVT5 and COOX1, were isolated from the geothermal soils of the Favara Grande on Pantelleria Island, Italy. Extended physiology studies were performed with K. spormannii FAVT5, and showed that this strain grows optimally at 55 °C and pH 5.0. The highest growth rate is obtained using H2 as energy source (µmax 0.19 ± 0.02 h-1, doubling time 3.6 hours). K. spormannii FAVT5 can additionally grow on a variety of organic substrates, including some alcohols, volatile fatty acids and amino acids. The genome of each strain encodes for two O2-tolerant hydrogenases belonging to [NiFe] group 2a hydrogenases and transcriptome studies using K. spormannii FAVT5 showed that both hydrogenases are expressed under H2 limiting conditions. So far no Firmicutes except K. spormannii FAVT5 have been reported to exhibit a high affinity for H2, with a Ks of 327 ± 24 nM. The genomes of each strain encode for one putative CO dehydrogenase, belonging to Form II aerobic CO dehydrogenases. The genomic potential and physiological properties of these Kyrpidia strains seem to be quite well adapted to thrive in the harsh environmental volcanic conditions.